Investigating the Competitive Advantage in the Green Bean Coffee Supplying Company Business: PT Trio Lestari - Adinegara, Marcel; Tan, Jacob Donald (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
Indonesia was the world's third largest coffee exporter with a total export volume of 1.2 million bags, while domestic coffee consumption in 2015/2016 made it the second largest exporter by total export volume. 1.2 million bags. This follows Brazil's coffee consumption of 4.5 million bags. Robusta accounts for 90% of domestic coffee raw material production, and Arabica accounts for the remaining 10% and it is still slowly growing to this day. Reflecting on the high demand coffee beans in the agriculturesideof the business especially in Indonesia,itis somehow an old fashioned and less talked about however a very interesting case on how the sector has been struggling to achieve a consistent growth and success. In recent years especially has been tough for the business because of predicted uncontrollable climate change and newcomers coming into the business. The researchers are using PT Trio Lestari as a respective case study to analyze the businesses' sector current stateand howits competitiveadvantageworkinthe challenges that the agriculture industry and its competitions has to offer. This research uses qualitative method with objective data collection and interviews with the subjects in various fields starting from its respective owners, employeesandto their business partners. The findings of this research are the latent variables that contributes into the competitive advantage of the company such as Entrepreneurial Journey Experiences, Personal Level B2B Partner’s Trust, Trustworthy Company Reputation, Good Relationship and Working Environment for Employees, The Sense of Familiness, Competitive Product Pricing, Convenience in Transactions and Services. The study will allow other potential research to dig deeper on the agricultural sector of the coffee business.